Tinjauan Yuridis Pembagian Harta Warisan Terhadap Anak Yang Berbeda Agama Dalam Kompilasi Hukum Islam dan KUHPerdata - Melia Indah Melani (Dinamika, 2021)
ABSTRACTIn Islamic Law the difference of religion between the heir and the heir can be a barrier to inherit, but in the civil Code of the difference between the testator and the heir are not a barrier. This paper raised the following problem formulation: 1. How does the division of the inheritance against children of different religions in the perspective of the Compilation of Islamic Law and civil Code? 2. How the comparison of the system of division of inheritance the children of the different religions in the perspective of the Compilation of Islamic Law and civil Code? The method used in this research is juridical normative. Between Islamic Law with the Civil Law there is a clear difference in governing the inheritance rights of different religions, where in Islamic Law the testator and the heirs should be embraced the same religion, namely the religion of Islam while in Civil Law there is no barrier in inherited, though there are differences of religion between the heir and his heir.Keywords: Bequests, Children, Different ReligionsABSTRAKDalam Hukum Islam perbedaan agama antara pewaris dan ahli waris dapat menjadi penghalang untuk mewarisi, tetapi dalam KUHPerdata perbedaan antara pewaris dan ahli waris tidak terdapat penghalang. Karya tulis ini mengangkat rumusan masalah sebagai berikut: 1. Bagaimana cara pembagian kewarisan terhadap anak yang berbeda agama dalam perspektif Kompilasi Hukum Islam dan KUHPerdata? 2. Bagaimana perbandingan sistem pembagian waris anak beda agama dalam perspektif Kompilasi Hukum Islam dan KUHPerdata? Metode yang digunakan dalam penelitian ini ialah yuridis normatif. Antara Hukum Islam dengan Hukum Perdata terdapat perbedaan yang jelas dalam mengatur hak waris berlainan agama, dimana dalam Hukum Islam pewaris dan ahli waris harus memeluk agama yang sama yaitu agama Islam sedangkan dalam Hukum Perdata tidak ada yang menjadi penghalang dalam mewarisi sekalipun terdapat perbedaan agama antara pewaris dan ahli warisnya.Kata Kunci: Harta Warisan, Anak, Beda Agama